NAVIGATING THE LEGAL LANDSCAPE OF DIGITAL NOMADISM: A SWISS PERSPECTIVE ON COMPLIANCE RISKS AND HR STRATEGIES - Bordiuh, Tetiana (Collection of scientific papers «ΛΌГOΣ», 2025)
Digital nomadism has reconfigured the geography of work, allowing employees to remain professionally active while living and traveling across borders. While this offers unmatched flexibility and lifestyle benefits, it also challenges traditional legal frameworks. From a Swiss legal standpoint, the extraterritorial presence of employees raises nuanced issues of taxation, labor law, social security, immigration, and data protection. Therefore, companies must balance flexibility with legal compliance to avert liability and reputational harm.